A confocal microwave imaging implementation for breast cancer detection - Nirmine Hammouch; Hassan Ammor (IAES Indonesian Section, 2019)
Breast cancer affects many women in many ways. Early diagnosis is the most important key for detecting malignant tissue. In this paper, we present the design of a microstrip patch antenna for ultra wide band (UWB) biomedical applications covering the full range of FCC frequencies (3.1 GHz to 14 GHz). We have used a single antenna with various positions to scan the whole breast phantom. A confocal microwave imaging (CMI) algorithm has been implemented and applied to create a 2D image of the tumor. The results obtained suggest the feasibility of using CMI method for detecting small breast tumors with high precision and more safety.